Blockade of GM-CSF pathway induced sustained suppression of myeloid and T cell activities in rheumatoid arthritis. (23rd October 2017) - Guo, Xiang; Higgs, Brandon W; Bay-Jensen, Anne-Christine; Wu, Yuling; Karsdal, Morten A; Kuziora, Michael; Godwood, Alex; Close, David; Ryan, Patricia C; Roskos, Lorin K; White, Wendy I
Abstract: Objectives: Targeting the granulocyte-macrophage colony-stimulating factor (GM-CSF) pathway holds great potential in the treatment of inflammatory diseases. Mavrilimumab, a human monoclonal GM-CSF receptor-α antibody, has demonstrated clinical efficacy in RA. Our current study aimed to elucidate mechanisms of action and identify peripheral biomarkers associated with therapeutic responses of GM-CSF antagonism in RA. Methods: A 24-week placebo (PBO)-controlled trial was conducted in 305 RA patients who received mavrilimumab (30, 100 or 150 mg) or PBO once every 2 weeks. Serum biomarkers and whole blood gene expression profiles were measured by protein immunoassay and whole genome microarray. Results: Mavrilimumab treatment induced significant down-regulation of type IV collagen formation marker (P4NP 7S), macrophage-derived chemokine (CCL22), IL-2 receptor α and IL-6 compared with PBO. Both early and sustained reduction of P4NP 7S was associated with clinical response to 150 mg mavrilimumab treatment. Gene expression analyses demonstrated reduced expression of transcripts enriched in macrophage and IL-22/IL-17 signalling pathways after GM-CSF blockade therapy. Myeloid and T cell-associated transcripts were suppressed in mavrilimumab-treated ACR20 responders but not non-responders. While CCL22 and IL-6 down-regulation may reflect a direct effect of GM-CSFR blockade on the production of pro-inflammatory mediators by myeloid cells, the suppression of IL-2 receptor α and IL-17/IL-22 associated transcripts suggests an indirect suppressive effect of mavrilimumab on T cell activation. Conclusion: Our results demonstrated association of peripheral biomarker changes with therapeutic response to mavrilimumab in RA patients. The sustained efficacy of mavrilimumab in RA may result from both direct effects on myeloid cells and indirect effects on T cell activation after GM-CSFR blockade.